ANALISIS PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVERNING - Lili Supriyadi (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2019)
This research is aimed to examine the influence of Leadership styles and Organizational culture to Job Satisfaction. It is also to study the effect of Job Satisfaction to Organizational Commitment and to test the Cultural Organization, Leadership Styles, and Job Satisfaction toward Employee's Performance using Organizational Commitment as intervening variable. The use of these variables are based on the previous research by Koesmono (2005), Kirk L. Rogga (2001), Yuwalliatin (2006), Masrukhin & Waridin (2006), Morrison (1997), Samad (2005), Shea, M. (1999) dan Lok, Peter (2004) which found the direct effect and indirect effect of Organizational Culture, Leadership Style toward Job Satisfaction, Job Satisfaction toward Organizational Commitment, and Organization Culture, Leadership Style and job satisfaction toward Employee's performance using Organizational Commitment to be variabel interverning. Theses variables enable us to solve problems in PT. Garda Jakarta. The sample of this research was 100 employees of PT. Garda Jakarta. Structural Equation Model (SEM) was run by AMOS software to analyze data. The result showedthat Leadership Styles and Cultural Organization gives positive significant influence to JobSatisfaction, Job Satisfaction gives significant influence to Organizational Commitment, Organization Culture gives significant influence to Employee's performance, leadership style gives influence to Employee's Performance, Organization Culture, Leadership Style, and Job Satisfaction contributes an significant influence to Employee's Performance using Organizational Commitment to be variabel interverning. This empirical result indicates that Leadership Styles and Organizational Commitment become one of many causes that trigger low Employee's Performance Job Satisfaction, and Cultural Organization. The company needs to consider Leadership Styles, Organizational Commitment in order to increase Employee's Performance because those factors proved depend on them. Theoritical implications and suggestions for future research have been elaborated at the end of this study.